PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP PADA RSUD KABUPATEN BANGGAI KEPULAUAN - ALIA, MAGVIRA (Fakultas Ekonomi Universitas Tadulako, 2015)
The study intends to determine simultaneous and partial influence of service quality (X) consisting of physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) on patient satisfaction (Y) in the General Hospital of Banggai Islands, where the study is located. The type of research is descriptive. Sources of data is primary data retrieved from questionnaires and secondary data obtained from documents of the Regional General Hospital Banggai Islands. The sample consists of 72 respondents. The sampling technique used is purposive sampling. Based on the results, it is shown that the quality of service (X), consisting of physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) simultaneously have significant influence on patient satisfaction (Y) of 69.60% while the remaining 30.40% is influenced by other causes. Partial test shows that there are three independent variables: physical evidence (X1), reliability (X2) and assurance (X4) that have non-significant influence to the patients? satisfaction at the General Hospital of Banggai Islands.